Impact of inhalational versus intravenous anaesthesia on early delirium and long-term survival in elderly patients after cancer surgery: study protocol of a multicentre, open-label, and randomised controlled trial. Issue 11 (28th November 2017) - Zhang, Yue; Li, Hui-Juan; Wang, Dong-Xin; Jia, Hui-Qun; Sun, Xu-De; Pan, Ling-Hui; Ye, Qing-Shan; Ouyang, Wen; Jia, Zhen; Zhang, Fang-Xiang; Guo, Yong-Qing; Ai, Yan-Qiu; et al.
Abstract : Introduction: Elderly patients who have solid organ cancer often receive surgery. Some of them may develop delirium after surgery and delirium development is associated with worse outcomes. Furthermore, despite all of the advances in medical care, the long-term survival in cancer patients is far from optimal. Evidences suggest that choice of anaesthetics during surgery, that is, either inhalational or intravenous anaesthetics, may influence outcomes. However, the impact of general anaesthesia type on the occurrence of postoperative delirium is inconclusive. Although retrospective studies suggest that propofol-based intravenous anaesthesia was associated with longer survival after cancer surgery when compared with inhalational anaesthesia, prospective studies as such are still lacking. The purposes of this randomised controlled trial are to test the hypotheses that when compared with sevoflurane-based inhalational anaesthesia, propofol-based intravenous anaesthesia may reduce the incidence of early delirium and prolong long-term survival in elderly patients after major cancer surgery. Methods and analysis: This is a multicentre, open-label, randomised controlled trial with two parallel arms. 1200 elderly patients (≥65 years but <90 years) who are scheduled to undergo major cancer surgery (with predicted duration ≥2 hours) are randomised to receive either sevoflurane-based inhalational anaesthesia or propofol-based intravenous anaesthesia. Other anaesthetics and supplemental drugs including sedatives, opioids and muscle relaxants are administered in both arms according to routine practice. The primary early outcome is the incidence of 7-day delirium after surgery and the primary long-term outcome is the duration of 3-year survival after surgery. Ethics and dissemination: The study protocol has been approved by the Clinical Research Ethics Committees of Peking University First Hospital (2015[869]) and all participating centres. The results of early and long-term outcomes will be analysed and reported separately. Trial registration number: ChiCTR-IPR-15006209; NCT02662257 ; NCT02660411 .